Publishing Research Articles in the international context: supervisors as literacy brokers - Junaid, Oluwatosin Mariam (2022)
In Brazil, similarly to other countries, there is a current trend in academia that research should be communicated in English to increase the chances of it being noticed by a geographically diverse scientific community(GEA-VALOR; REY-ROCHA; MORENO, 2014). This has placed higher education students under immense pressure to publish articles in the English language. Additionally, some postgraduate programs have attached the publication of articles in English journals as a partial requirement for graduation (MARTINEZ; GRAF, 2016). Brazil\'s first language is not English, and there are limited resources available to assist students with their writing process in the English language (FERREIRA; LOUSADA, 2016). As a consequence, postgraduate students tend to depend on their supervisors to navigate their writing process(HABIBIE; HYLAND, 2018). Therefore, this study aimed to give insights and raise awareness on supervisors\' literacy brokering activities by examining how they try to ensure that their supervisees write papers with a high probability of getting published. Literacy brokers are those who contribute to the development of a text intended for publication(LILLIS; CURRY, 2006). Data was collected through text histories and semi-structured interviews. Text histories were used to investigate the focus of supervisors\' feedback when students write for publications in the English Language. It was also used to track how supervisors\' feedback brought about textual progressions to students\' writing process. The semi-structured interviews were used to understand the challenges encountered by supervisors during the feedback process. Semi structures interviews were also used to clarify issues that arose from the analysis of text histories. Data were analyzed using thematic data analysis. The study consisted of ten participants, which comprised seven postgraduate students and three supervisors. Overall, the results showed that supervisors focused on aspects of their supervisees\' texts that they considered essential to develop their texts. The focus of supervisors\' feedback determined the type of written feedback given (direct or indirect written feedback). Supervisors\' feedback also enabled their supervisees to understand the strengths and weaknesses of their texts, therefore aiding the revision process. The study also brought the challenges encountered by supervisors during the feedback process to the fore. The study showed that supervisors play critical roles in their supervisees\' writing process from conception until submission, which categorizes them as literacy brokers. Pedagogical support should be provided to supervisors to enable them to mitigate their challenges.